A Comparative Study on the Effectiveness of Paracervical Block and Diclofenac Versus Paracervical Block and Pentazocine for Analgesia During Manual Vacuum Aspiration - Usman, Malgwi J.; Nwachukwu, C. N.; Alu, F. E.; Ozori, Ebiogbo S.; Okpara, Abuchi L.; Usman, Yelwa; Alabintei, Ochuko M.; Ogidigba, Peter I. (British Journal of Healthcare and Medical Research, 2022)
Management of incomplete abortion with the use of manual vacuum aspiration is associated with pain. A good pain relief option is necessary during the procedure to improve the outcome and increase patients’ satisfaction. The study was aimed atdetermining and comparing the effectiveness of combining paracervical block with pentazocine and paracervical block with diclofenac as pain relief during manual vacuum aspiration for first-trimester incomplete abortion. This study involved 100 eligible women with the diagnosis of first-trimester incomplete abortion. Half of the participants were given paracervical block and intramuscular pentazocine 60 mg stat while the other half were given paracervical block and intramuscular diclofenac 75 mg stat before the manual vacuum aspiration procedure. The intensity of pain during the procedure was assessed using the Visual Analogue Scale (VAS). The level of significance was set at p value<0.05. The mean pain intensity was significantly higher in the diclofenac group than in the pentazocine group. From the study it was concluded that intramuscular pentazocine used as an adjunct to paracervical block during manual vacuum aspiration when compared to intramuscular diclofenac as an adjunct to paracervical block was found to be a more effective method of pain relief. The patient’s level of satisfaction was same in both study arms. However, participants in the pentazocine arm had more side effects.